Awareness and knowledge effectiveness of artificial intelligence module for digital technology programme - Alias, Suriana; Abdul Wahid, Khalid; Ab Aziz, Nasuhar; Wan Ramli, Wan Kairiah Hulaini; Mat Nawi, Nur Ainatul Mardiah; Abdullah, Nurulannisa; Abdullah, Murtadha (Journal of Islamic, Social, Economics and Development, 2026)
This study evaluates the effectiveness of a digital technology awareness programme focusing on Artificial Intelligence (AI), Blockchain, and Cryptocurrency (Crypto). The programme aimed to improve participants' knowledge and awareness of emerging technologies that are increasingly important in the digital economy. A quantitative pre-test and post-test design was employed using a structured questionnaire based on a five-point Likert scale. Participants completed the questionnaire before and after the programme, allowing changes in knowledge levels to be measured. The findings revealed significant improvements across all three programme modules. Average post-programme scores for AI, Blockchain, and Cryptocurrency increased substantially compared with the pre-programme assessment, indicating enhanced understanding of concepts, applications, benefits, and challenges related to these technologies. Overall, the programme effectively strengthened participants' digital literacy and awareness of emerging technologies, demonstrating the value of educational initiatives in preparing individuals for digital transformation and Industry 4.0.